Aortic dissection detection risk score has high sensitivity with moderate inter‐rater reliability. (16th August 2018) - Rotella, Joe‐Anthony; Goel, Vishal; Chan, Thomas; Yeoh, Michael; Taylor, David McD
Abstract: Objective: To retrospectively assess the accuracy and inter‐rater reliability of the aortic dissection detection risk score (ADD‐RS). Methods: Single‐centre, observational, diagnostic accuracy study undertaken in a university‐affiliated, tertiary hospital ED. Results: Two hundred patients were enrolled. Five patients were diagnosed with acute aortic dissection and had an elevated ADD‐RS >0. The ADD‐RS was 100% sensitive with a negative and positive predictive values of 100% (if ADD‐RS ≥1). Inter‐rater reliability was moderate (Kappa = 0.55). Conclusion: The ADD‐RS was highly sensitive in our cohort. Further work to evaluate the score prospectively and in combination with a D‐Dimer is required.